Inovasi Terbaru dalam Terapi Gen, Terapi Berbasis Sel, dan Pengembangan Obat Anti Kanker dari Bahan Alam - Muthiya Amalia; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Cancer therapy has undergone remarkable advancements in recent decades, driven by innovations in gene therapy, cell-based therapy, and the development of anti-cancer drugs from natural products. Gene therapy offers the possibility of correcting genetic mutations that cause cancer, while cell-based therapies, such as CAR-T cell therapy, provide personalized and effective solutions. Additionally, the exploration of natural compounds continues to be a promising approach in anti-cancer drug development. This paper discusses recent progress in these three fields, highlighting their potential, challenges, and implications for future clinical applications.